Impact of Length and Percent Dosage of Recycled Steel Fibers on the Mechanical Properties of Concrete - Akhtar Gul; Bashir Alam; Muhammad Junaid Iqbal; Wisal Ahmed; Khan Shahzada; Muhammad Haris Javed; Ezaz Ali Khan (Salehan Institute of Higher Education, 2021)
The global rapid increase in waste tyres accumulation, as well as the looming social and environmental concerns, have become major threats in recent times. The use of Recycled Steel Fiber (RSF) extracted from waste tyres in fiber reinforced concrete can be of great profitable engineering applications however the choice of suitable length and volume fractions of RSF is presently the key challenge that requires research exploration. The present experimental work aims at investigating the influence of varying lengths (7.62 and 10.16 cm) and dosages (1, 1.5, 2, 2.5, 3, 3.5, and 4%) of RSF on the various mechanical properties and durability of concrete. Test results revealed that the varying lengths and dosages of RSF significantly affect the mechanical properties of concrete. The improvements in the compressive strength, splitting tensile strength, and Modulus of Rupture (MOR) of RSF reinforced concrete observed were about 26, 70, and 63%, respectively. Moreover, the RSF reinforced concrete showed an increase of about 20 and 15% in the yield load and ultimate load-carrying capacity, respectively. The durability test results showed a greater loss in compressive strength and modulus of elasticity and a smaller loss in concrete mass of SFRC. Based on the experimental findings of this study, the optimum dosages of RSF as 2.5 and 2% for the lengths 7.62 and 10.16 cm lengths, respectively are recommended for production of structural concrete. Doi: 10.28991/cej-2021-03091750 Full Text: PDF